(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article examines the impact of sensory integration therapy on the development of social skills in children with autism spectrum disorder. Research findings indicate that the therapy significantly improves eye contact, emotional regulation, communication responses, and joint play behavior. SIT is recommended as an effective intervention to support social adaptation in children with ASD.